2020
DOI: 10.1109/tbme.2019.2911423
|View full text |Cite
|
Sign up to set email alerts
|

Hearables: Automatic Overnight Sleep Monitoring With Standardized In-Ear EEG Sensor

Abstract: Objective: Advances in sensor miniaturisation and computational power have served as enabling technologies for monitoring human physiological conditions in real-world scenarios. Sleep disruption may impact neural function, and can be a symptom of both physical and mental disorders. This study proposes wearable in-ear electroencephalography (ear-EEG) for overnight sleep monitoring as a 24/7 continuous and unobtrusive technology for sleep quality assessment in the community. Methods: Twenty-two healthy participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 44 publications
1
63
0
1
Order By: Relevance
“…There are several possible applications of recycling the muscle tone information from the EEG signal. Recently, an increasing number of wearable biosignal amplifiers have been developed (e.g., around ear applications, wearable headbands) to obtain large-scale data and allow for in-field, long-term assessments of sleep [7][8][9]. One important aspect of these wearable devices is a non-obtrusive design and therefore a reduction of electrodes is desired.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several possible applications of recycling the muscle tone information from the EEG signal. Recently, an increasing number of wearable biosignal amplifiers have been developed (e.g., around ear applications, wearable headbands) to obtain large-scale data and allow for in-field, long-term assessments of sleep [7][8][9]. One important aspect of these wearable devices is a non-obtrusive design and therefore a reduction of electrodes is desired.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the raw data might be dumped from the commercial polysomnogram (PSG) and the raw data might have been filtered at the frequency range 0.3-35 Hz. Due to the advance of technology and focus on large-scale applications, there is an increasing number of mobile devices capable of recording EEG signal in in-home settings (e.g., single channel amplifiers on the forehead or in-ear/around ear applications) [6][7][8][9]. These mobile solutions might not include EMG and EOG information, and the raw data might be bandpassed for different purposes, like data storage or transmission.…”
Section: Introductionmentioning
confidence: 99%
“…vital signs and neural function, as the head does not move much in daily life unlike sites such as the wrist. Owing to these desirable properties, the ear-canal has been established as a feasible wearable site by Ear-EEG [ 15 , 16 ] and Ear-ECG [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In ear, EEG is a modality that has shown promise in recent years, for instance, Mikkelsen et al 62 compared in-ear mobile EEG analysed through machine learning-based automated scoring to conventional, manual scored PSG and commercial-grade actigraphy showed promising results, although also constrained to a laboratory environment. A 2019 study showed that automatic sleep stage prediction based on a single in-ear sensor demonstrated a 74% agreement with the hypnogram generated from full PSG, which is promising but still requires further work for it to be at a clinical standard of performance (90% agreement) 63 . These devices are particularly interesting given their potential for freeliving application.…”
Section: Sleep Monitoring Outside the Laboratorymentioning
confidence: 99%